Elucidating Redox-Level Dispersion and Local Dielectric Effects within Electroactive Molecular Films - Buono, Paulo R. [UNESP]; Davis, Jason J. (Amer Chemical Soc, 2014)
The electron exchange between a redox-active molecular film and its underlying electrode can be cleanly tracked, in a frequency-resolved manner, through associated capacitive charging. If acquired data is treated with a classical (non quantum) model, mathematically equivalent to a Nernst distribution for one redox energy level, redox site coverage is both underestimated and environmentally variable. This physically unrealistic model fails to account for the energetic dispersion intrinsically related to the quantized characteristics of coupled redox and electrode states. If one maps this redox capacitive charging as a function of electrode potential one not only reproduces observations made by standard electroanalytical methods but additionally and directly resolves the spread of redox state energies the electrode is communicating with. In treating a population of surface-confined redox states as constituting a density of states, these analyses further resolve the effects of electrolyte dielectric on energetic spread in accordance with the electron-transfer models proposed by Marcus and others. These observations additionally underpin a directly (spectrally) resolved dispersion in electron-transfer kinetics.